2019
DOI: 10.1002/adfm.201901806
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable Polymers: Mechanical Properties Improvement by Balancing Intra‐ and Intermolecular Interactions

Abstract: The mechanical properties of polymers are highly dependent on the mobility of the underlying chains. Changes in polymer architecture can affect inter‐ and intramolecular interactions, resulting in different chain dynamics. Herein, an enhancement in the mechanical properties of poly(butylmethacrylate) is induced by folding the polymer chains through covalent intramolecular crosslinking (CL). Intramolecular CL causes an increase in intramolecular interactions and inhibition of intermolecular interactions. In bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…More recently, we have also shown that reversible noncovalent interactions used for intramolecular collapse present an additional advantage—due to entropic spring effects, these sacrificial bonds can reform after mechanical unfolding, leading to even longer property lifetimes . In the solid state, we have shown that intramolecular collapse leads to additional advantages—significant improvements in moduli, stretchability, and toughness …”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…More recently, we have also shown that reversible noncovalent interactions used for intramolecular collapse present an additional advantage—due to entropic spring effects, these sacrificial bonds can reform after mechanical unfolding, leading to even longer property lifetimes . In the solid state, we have shown that intramolecular collapse leads to additional advantages—significant improvements in moduli, stretchability, and toughness …”
Section: Introductionmentioning
confidence: 94%
“…As in our recent studies, 9,23 the chemistry chosen for intramolecular folding is grounded on the Michael addition of poly(MMA) [(PMMA)-co-AEMA], 24 since it offers a simple and reliable crosslinking chemistry which can be easily followed by NMR. 8,10,14 Hence, a large batch of a linear PMMA-co-AEMA SCHEME 1 Synthesis of SCPNs having intramolecular CLs with different lengths.…”
Section: Crosslinker Lengthmentioning
confidence: 99%
See 3 more Smart Citations